The Promises and Prospects of Geography in Higher Education - Kong, Lily (Institutional Knowledge at Singapore Management University, 2007)
The idea for this JGHE symposium came to me as I reflected on the spatial turn in the humanities and social sciences, and felt encouraged by the growing influence of geography in the intellectual spaces of other disciplines. Amidst positive thoughts, I wondered if the institutional position of the discipline had strengthened with its recently enhanced intellectual position, and what the geography of geography's institutional presence and strength was. For sure, anecdotal stories circulate regarding the opening or closure of a geography department, a renaming, a split and so forth…. A symposium of papers from different parts of the world would be helpful to offer considered evidence to support or isolate anecdotal stories concerning where geography was heading, as well as to put into wider perspective why certain trends have been observed in particular parts of the world.